Engineering Education for a Smart Society World Engineering Education Forum & Global Engineering Deans Council 2016 - Auer, Michael E.; Kim, Kwang-Sun.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents selected papers from the 'World Engineering Education Forum & Global Engineering Deans Council,' held in November 2016 in Seoul, Korea. The massive changes currently underway in all areas of society, especially in engineering (and consequently in engineering education), call for new pedagogic qualifications and approaches. To face these current real-world challenges, higher education has to find innovative ways to quickly respond to these new needs. The papers gathered here address three essential problems: - The main approach to engineering in the 21st century is collaboration - at many levels, within universities or colleges, between institutions, and on a global scale. At the same time, we need a new quality of collaboration between academia, industry, professional and governmental organizations. - The complexity of engineering projects and solutions is rapidly growing, and increasingly includes non-technical aspects. - One of the key tasks for future engineers will be the development of a sustainable society, which is essential to keeping the global environment in balance.
The Empirical Research on Human Knowledge Processing in Natural Language within Engineering Education -- Study on Interest and Perception of Value in Multinational Collaborative Design Projects Among Engineering Students -- Managing Industry Sponsored Capstone for Learning & Customer Satisfaction -- The Content and Structure of Engineering Ethical Codes in China -- A Study on the Educational Effectiveness of the Industry Professional Practice (IPP) Program -- Introducing Responsible Resource Management to the Engineering Education -- Recruiting and Developing Academic Leaders -- Picking Low Hanging Fruits-Integrating Multidisciplinary Learning in Traditional Engineering Curricula by Interdisciplinary Project Courses -- Metacognitive Development In Engıneerıng Students Through Cooperatıve Problem Based Learnıng (CPBL) -- Theoretical Foundations of Vocational and Technical Education and the part they play in the process of State Building.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence